2014
DOI: 10.1103/physrevc.90.044312
|View full text |Cite
|
Sign up to set email alerts
|

αdecay ofAu176

Abstract: The isotope 176 Au has been studied in the complete fusion reaction 40 Ca + 141 Pr → 176 Au + 5n at the velocity filter SHIP (GSI, Darmstadt). The complex fine-structure α decay of two isomeric states in 176 Au feeding several previously unknown excited states in the daughter nucleus 172 Ir is presented. An α-decay branching ratio of b α = 9.5(11)% was deduced for the high-spin isomer in 172 Ir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…The results of the present high-spin study of states in 168 Re aides in the spin (tentatively assigned 6 + in Ref. [1]) and configuration assignments of the isomers observed in the high-spin chain. In addition, a recent publication of the first rotational structures in 166 Re [2], the lightest odd-odd rhenium nucleus with known excitations, reported two γ-ray decay sequences.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…The results of the present high-spin study of states in 168 Re aides in the spin (tentatively assigned 6 + in Ref. [1]) and configuration assignments of the isomers observed in the high-spin chain. In addition, a recent publication of the first rotational structures in 166 Re [2], the lightest odd-odd rhenium nucleus with known excitations, reported two γ-ray decay sequences.…”
Section: Introductionsupporting
confidence: 54%
“…This is consistent with the h 11/2 quasiproton contributing ∼1.4 of alignment to the πh 11/2 ν(h 9/2 /f 7/2 ) configuration; therefore, the I π = 7 + spin/parity assignment for the lowest spin state of band 2 appears to be appropriate. In addition, the recent α-decay work of Andreyev et al [1] observed a single decay from the high-spin 7…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations